2021
DOI: 10.3390/nu13051461
|View full text |Cite
|
Sign up to set email alerts
|

Can Mixed Strains of Lactobacillus and Bifidobacterium Reduce Eczema in Infants under Three Years of Age? A Meta-Analysis

Abstract: (1) Background: Whether early supplementation of probiotics to improve intestinal flora can effectively prevent eczema remains a controversial issue. We aimed to investigate the effect of a mixed strain of Lactobacillus and Bifidobacterium on eczema in infants under three years old at present; (2) Methods: We searched the databases of PubMed, Web of Science, and Cochrane Library, as well as National Knowledge Infrastructure (CNKI), WeiPu (VIP), and WanFang Data (WanFang) for randomized controlled trials (RCTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In addition, the preventive effect of probiotics on pediatric AD is better than that of treatment ( Lee et al., 2008 ). A mixture of Lactobacillus and Bifidobacteria can effectively reduce the incidence of eczema in infants and young children during the first three years of life ( Sun et al., 2021 ). The preventive effects of probiotics on eczema appear to last until age of two ( Dang et al., 2013 ) and extend to the age four years ( Kuitunen, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the preventive effect of probiotics on pediatric AD is better than that of treatment ( Lee et al., 2008 ). A mixture of Lactobacillus and Bifidobacteria can effectively reduce the incidence of eczema in infants and young children during the first three years of life ( Sun et al., 2021 ). The preventive effects of probiotics on eczema appear to last until age of two ( Dang et al., 2013 ) and extend to the age four years ( Kuitunen, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both Lactobaccillus and Bifidobacterium are probiotics. Recent studies showed that early life exposure to these strains can reduce the risk of AD ( 34 ). However, the results of the studies in support of this hypothesis are still inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“… 55 discovered that probiotics could relieve AD symptoms, especially using mixed‐strain probiotics ( Lactobacillus and Bifidobacterium). Another meta‐analysis 56 also favored that mixed strains of Lactobacillus and Bifidobacterium could reduce the incidence of AD. Thus, a mixed‐strain probiotic component might be beneficial to patients with AD.…”
Section: Discussionmentioning
confidence: 99%